General and Specific Effects of Stereo Learning - Xi, Jie; Wang, Ge-Tong; Zhao, Jin; Huang, Chang-Bing (Frontiers in Human Neuroscience, 2021)
Technological advancements in virtual reality challenge human vision, especially stereopsis, a function that characterizes how the two eyes coordinate to form a unified 3-D representation of external world and is deficient in 30% normal population. Although previous studies have consistently found that perceptual learning of stereopsis significantly improved stereoacuity, the underlying mechanism of stereo learning remains heavily debated. Here, we trained subjects with normal stereo vision (assessed with the FLY Stereo Acuity Test) to judge stereopsis containing three types of binocular disparity orders (i.e., zero-, first-, and second-order), aiming to systematically examine the characteristics and plasticity of stereo learning. Thirty subjects were randomly assigned into three training groups (each for zero-, first-, or second-order disparity, separately). The disparity thresholds were measured before and after training. Disparity threshold was measured in ten additional control subjects only at the pre- and post-training phases. Stereoscopic images were displayed through a shutter goggle synchronized to a monitor. We found that training significantly improved the zero-, first-, and second-order disparity thresholds by 52.42%, 36.28%, and 14.9% in the zero-order training condition, respectively; 30.44%, 63.74%, and 21.07% in the first-order training condition, respectively; and 30.77%, 25.19%, and 75.12% in the second-order training condition, respectively. There was no significant improvement in the control group. Interestingly, the greatest improvements in the first-order and second-order disparity thresholds were found in the corresponding disparity training group; on the contrary, improvements in the zero-order disparity threshold were comparable in all three disparity training groups. Our findings demonstrated both general (related to zero-order disparity) and specific improvements (related to first- and second-order disparity) in stereo learning, suggesting that stereo training occurs at different visual processing stages and the effects of training might depend on the specific training sites.